PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PBL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT BAGI SISWA KELAS VI SDN KAMBANGAN 01 - Slamet Yani Budhiyati; Rasiman; Joko Sulianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problems in this research are (1) how is the validity of the PBL learning tools developed to improve critical thinking of addition and subtraction of integers for students of class VI at SDN Kambangan 01? how practical is the PBL learning tool developed to improve critical thinking of addition and subtraction of integers for class VI students at SDN Kambangan 01? how effective is the PBL learning tool to improve critical thinking of addition and subtraction of integers for class VI students at SDN Kambangan 01?. The aims of this study were (1) to develop and produce valid PBL learning tools to improve critical thinking in addition and subtraction of integers for sixth grade students at SDN Kambangan 01, (2) to develop and produce practical PBL learning tools to improve addition and critical thinking reduction of integers for class VI students at SDN Kambangan 01, (3) Develop and produce effective PBL learning tools to improve critical thinking by adding and subtracting integers for class VI students at SDN Kambangan 01. The subjects in this study were 34 students in class VI at SDN Kambangan 01 and SDN Kambangan 02. Data collection methods used are questionnaires, documentation and tests to students at the beginning and end of learning. Data analysis used was descriptive analysis, pre-requisite test, and hypothesis testing. From the results of the study it can be seen that PBL-based Mathematics learning tools in the form of lesson plans, textbooks, worksheets, learning media, and learning outcomes assessment instruments on aspects of learning objectives achieve very high criteria. valid, aspects of learning materials achieve very valid criteria, aspects of learning strategies are said to be valid, aspects of selecting learning media achieve valid criteria, selection of materials and learning resources achieve very valid criteria, and learning evaluation achieves very valid criteria. PBL-based Mathematics learning tools were declared practical because two indicators were achieved, namely the teacher's response was in the positive category with an achievement of 82.5% and student responses were in a very positive category with an achievement of 86.61%. The PBL-based mathematics learning tool was declared effective because three indicators were achieved, namely student learning outcomes achieving 90% completeness in the very good category with an average student score of 84.24 in the good category, students' critical thinking skills in the pre-test of 79.97% in the good category and at the post test it increased to 86.125% in the very good category, and the teacher's ability to manage learning in the very good category, namely 88.75%.